TDP-43 and RNA form amyloid-like myo-granules in regenerating muscle. (22nd November 2018) - Vogler, Thomas; Wheeler, Joshua; Nguyen, Eric; Hughes, Michael; Britson, Kyla; Lester, Evan; Rao, Bhalchandra; Betta, Nicole; Whitney, Oscar; Ewachiw, Theodore; Gomes, Edward; Shorter, James; et al.
Abstract A dominant histopathological feature in neuromuscular diseases, including amyotrophic lateral sclerosis and inclusion body myopathy, is cytoplasmic aggregation of the RNA-binding protein TDP-43. Although rare mutations inTARDBP —the gene that encodes TDP-43—that lead to protein misfolding often cause protein aggregation, most patients do not have any mutations inTARDBP . Therefore, aggregates of wild-type TDP-43 arise in most patients by an unknown mechanism. Here we show that TDP-43 is an essential protein for normal skeletal muscle formation that unexpectedly forms cytoplasmic, amyloid-like oligomeric assemblies, which we call myo-granules, during regeneration of skeletal muscle in mice and humans. Myo-granules bind to mRNAs that encode sarcomeric proteins and are cleared as myofibres mature. Although myo-granules occur during normal skeletal-muscle regeneration, myo-granules can seed TDP-43 amyloid fibrils in vitro and are increased in a mouse model of inclusion body myopathy. Therefore, increased assembly or decreased clearance of functionally normal myo-granules could be the source of cytoplasmic TDP-43 aggregates that commonly occur in neuromuscular disease. Cytoplasmic, amyloid-like oligomeric assemblies that contain TDP-43 are increased in damaged tissues with elevated regeneration, thereby enhancing the possibility of amyloid fibre formation and/or aggregation of TDP-43 in disease.